In vitro Antifungal Effect of Caspofungin-Fluconazole Sequential Treatment Against Mixed Candida albicans and Candida glabrata Biofilm - Pesee, Siripen; Wohyeh, Kasma; Srisuk, Kusuma; Poomgate, Baifern; Umpreecha, Chalapinyo; Arpornsuwan, Teerakul (Thai Journal of Science and Technology, 2019)
Candidiasis is the most prevalence opportunistic fungal infection of humans, and invasive Candida infections remain an important cause of morbidity and mortality, especially in hospitalized and immunocompomised patients. Recent investigation revealed that simultaneous combination of caspofungin and fluconazole appeared to affect the quantity and cell architecture of C. albicans and C. glabrata mixed biofilm in vitro. The objective of this study was to further investigate the effect of caspofungin (CAS) sequentially combined with fluconazole (FLU) on the vitality and quantity of mixed C. albicans and C. glabrata biofilm. Viability of biofilms was evaluated by 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5[(phenylamino)carbonyl)]-2H-tetrazolium hydroxide (XTT) assay and biomass of biofilm was assessed by crystal violet assay. The inhibitory effects of sequential CAS-FLU combinations on the biomass of biofilm were significantly declined when mixed biofilms were pretreated with FLU for a longer period of time over 3 h (p < 0.001), however, the vitality of FLU-pre exposed mixed biofilms in response to CAS-FLU combination treatment were not different. The biomass reduction effect of CAS-FLU combinations was dependent on the sequence of initial of drugs combination and the pre-exposure time. Conclusion, sequential CAS-FLU combinations treatment had an impact on the biomass but not viability of mixed C. albicans and C. glabrata biofilm.